2001
DOI: 10.1097/00007435-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Sentinel Clinic Survey of Chlamydia trachomatis Infection in Finland

Abstract: C trachomatis infection is spread all over Finland, and the risk factors include younger age, high number of sex partners, and use of oral contraceptives or IUDs. Source partner analysis focused attention on the importance of transmission from regular partners, especially in women. The time from transmission to diagnosis was long, and any effort to shorten this period would be an effective preventive strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…The rate in Finland was lowest among the oldest women, which is consistent with earlier studies(Hiltunen- Back et al 2001;Hiltunen-Back et al 2003).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The rate in Finland was lowest among the oldest women, which is consistent with earlier studies(Hiltunen- Back et al 2001;Hiltunen-Back et al 2003).…”
supporting
confidence: 92%
“…Many studies have shown the relation between socioeconomic characteristics and sexual behaviour. Various studies conducted in different populations have shown that young age (Khryanin 2004;Hiltunen-Back et al 2001), being unmarried or cohabiting (Radcliffe et al 2001;Nikula et al 2007) and having low education (Nikula et al 2007) are associated with gonorrhoea and chlamydial infection. Behavioural risk factors include early age at first sexual contact (Khryanin 2004), high number of sexual partners (Uuskula et al 2008;Khryanin 2004;Hiltunen-Back et al 2001;Nikula et al 2007), and not using condoms (Gallo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Factors identified as being independently associated with Chlamydia trachomatis in the final multiple logistic model were younger age (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) …”
Section: Discussionmentioning
confidence: 99%
“…The main risk factors reported in the literature as associated with C. trachomatis infections are age below 25 years-old, inconsistent condom use, multiple sexual partners, a new partner in the preceding 60 days and a history of STD 11,19,20 . In this study, an association among younger men (15-24 years-old) with infections was identified, but no association with reporting more than one partner in the preceding 12 months, inconsistent condom use and previous STD was included in the final model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation